2014
DOI: 10.1007/s10495-014-1021-0
|View full text |Cite
|
Sign up to set email alerts
|

ClC-3 deficiency protects preadipocytes against apoptosis induced by palmitate in vitro and in type 2 diabetes mice

Abstract: Palmitate, a common saturated free fatty acid (FFA), has been demonstrated to induce preadipocyte apoptosis in the absence of adipogenic stimuli, suggesting that preadipocytes may be prone to apoptosis under adipogenic insufficient conditions, like type 2 diabetes mellitus (T2DM). ClC-3, encoding Cl(-) channel or Cl(-)/H(+) antiporter, is critical for cell fate choices of proliferation versus apoptosis under diseased conditions. However, it is unknown whether ClC-3 is related with preadipocyte apoptosis induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 51 publications
(79 reference statements)
4
18
0
Order By: Relevance
“…A high level of ClC-3 alone is sufficient to cause Nox-derived ROS production. It has been shown that ClC-3 expression is upregulated in various cardiovascular diseases featured by increased oxidative stress, including hypertension [29], atherosclerosis [8], and diabetes [30]. Consistently, our present study also showed an increase in ClC-3 expression in Ang II-treated endothelial cells.…”
Section: Discussionsupporting
confidence: 91%
“…A high level of ClC-3 alone is sufficient to cause Nox-derived ROS production. It has been shown that ClC-3 expression is upregulated in various cardiovascular diseases featured by increased oxidative stress, including hypertension [29], atherosclerosis [8], and diabetes [30]. Consistently, our present study also showed an increase in ClC-3 expression in Ang II-treated endothelial cells.…”
Section: Discussionsupporting
confidence: 91%
“…As shown in table 4, the Xyl-B treatment significantly improved the neurological outcome of the tMCAO mice compared with that of the vehicle group (P<0.05 vs Vehicle controls, n=7 mice/group). Consistently, the tMCAO mice that were treated with edaravone also displayed significant neuroprotective effects compared with the vehicle control Xyl-B decreased the ROS level and increased the SOD2 level Reactive oxygen species (ROS) and reactive nitrogen species (RNS), such as nitric oxide (NO), play a key role in the pathophysiological response of the brain after an ischemia injury [20] . Here, we detected the total ROS levels by DHE staining.…”
Section: Xyl-b Improved the Neurological Outcomementioning
confidence: 74%
“…Quantitative real-time PCR The quantitative real-time PCR experiment was conducted as described previously [20] . Briefly, the total RNA from the ischemic region was isolated using the TRIzol reagent (Invitrogen).…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that ROS plays a key role in the pathophysiological response of the brain after I/R injury [32] . The results showed that I/R injury significantly increased ROS production compared to the normal rats.…”
Section: X1s Reduces the Level Of Reactive Oxygen Species (Ros) In Imentioning
confidence: 99%